Gatekeeping Perspektif Bruce Westle and Malcolm Mclean Dalam Produksi Berita Online www.wonogirikab.go.id - Izma, Arnitaa; Yatno, Tri; Putro, Adi Nugroho Susanto (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The Wonogiri Regency Government has a website called www.wonogirikab.go.id, which every day provides information in the form of news, appeals, or announcements. The content presented is in the form of activities by Regional Apparatus Organizations (OPD), the regent's agenda, and Wonogiri Regional government programs. From this, the media needs to filter incoming information through a strategy called gatekeeping. This gatekeeping strategy aims to reduce media inaccuracies in presenting news. In this research, the author uses the gatekeeping theory of Bruce Westley and Malcolm McLean which emphasizes the role of a gatekeeper. Gatekeepers are individuals who carry out gatekeeping from pre-production to post-production of online news. Research method through case studies. Data collection techniques include documentation, interviews, and observation. Data analysis uses the Miles and Huberman model, including data collection, data reduction, data presentation, and drawing conclusions. The results of research in the field showed that in the gatekeeping process from pre-production to post-production of news on the website www.wonogirikab.goid, the duties of a reporter and editor were only carried out by one person. Pre-production starts with determining news criteria, team discussions, and on-location coverage. The production process is carried out by cameramen and reporters when looking for information. Lastly, post-production is the editing stage by the editor and approval by the Head of the Wonogiri Regency Communication and Information Service.